発達期の低酸素状態は脳内の発達障害関連部位においてアストロサイトを低下させる - 冨田, 修平; 徳留, 健太郎; 山口, 雄大; 松永, 慎司; 植木, 正明 (日本薬理学会年会要旨集, 2021)
The fetal hypoxia such as threatened abortion is one of the risk factors for neurodevelopmental disorder. To clarify the pathophysiological mechanism in onset of these disease caused by hypoxic stress, we generated a rat model of fetal hypoxic stress and analyzed the expression level of astrocytes in developmental disorder-related region. Pregnant F344 rats were treated with subchronic hypoxia stress. After birth, rats were reared in normal home cage and behavioral tests were performed. After behavioral tests, rat brains were removed and used for immunohistochemical staining with glial fibrillary acidic protein (GFAP), which is a marker protein of astrocytes. In behavioral tests, the time of social behavior was significantly shortened in fetal hypoxia stress-loaded rats (hypoxia rats) compared to that of control rats. In addition, hypoxia rats showed disruption of learning and memory function. Furthermore, immunohistochemical staining revealed that the number of GFAP positive cells was significantly decrease in the neurodevelopmental disease-related regions in hypoxia rats. These results indicated that decrease of astrocytes in such brain area might cause disruption of neural informational transmission, which showed neurodevelopmental disorder-like behavioral phenotypes.